The Chariot, Communities, and State: Negotiating Heritage Governance in the Bungadya Jatra - Gnawali, Bikash (NPRC Journal of Multidisciplinary Research, 2026)
The Bungadya Jatra, also known as the Rato Matsyendranath Festival, is one of the most important living traditions in Nepal, dating back to the 7th century. While the local Newar community is still very much involved in keeping these rituals alive, the physical side of the festival is under a lot of pressure. The massive 60-foot wooden chariot, the traditional parade routes, and ancient objects are all being affected by changing government rules and the fast growth of cities. This research looks at the festival as a special case study, using policies and cultural observations from 2025. It also examines national laws and local city rules. The findings show that the main problems do not come from a lack of rules, but rather from too many different policies and organizations all trying to manage the same things. The study identifies a few major conflicts. For example, there is a constant struggle between keeping the chariot safe and dealing with new buildings that block its path. There is also a tension between the community’s need to perform rituals freely and the government’s desire to regulate everything. Essentially, protecting the Bungadya Jatra is a constant "negotiation." To keep this tradition going for future generations, the paper suggests that Nepal needs more coordinated policies that actually listen to local people and respect their traditional values.